Preliminary Findings on the Salivary Metabolome of Hookah and Cigarette Smokers - Greenfield, Ellen; Alves, Mariana de Sá [UNESP]; Rodrigues, Fernanda; Nogueira, Júlia Oliveira; da Silva, Letícia Ferrari; de Jesus, Henrique Pereira; Cavalcanti, Desiree Rosa; Carvalho, Bruna Fernandes do Carmo [UNESP]; Almeida, Janete Dias [UNESP]; Mendes, Maria Anita; Oliveira Alves, Mônica Ghislaine [UNESP] (American Chemical Society (ACS), 2023)
The aim of the study was to evaluate the salivary metabolomic profile of patients who habitually smoke hookah and cigarettes. The groups consisted of 33 regular and exclusive hookah smokers, 26 regular and exclusive cigarette smokers, and 30 nonsmokers. Unstimulated whole saliva was collected for the measurement of salivary metabolites by gas chromatography coupled with tandem mass spectrometry (GC-MS/MS). The MetaboAnalyst software was used for statistical analysis and evaluation of biomarkers. 11 smoking salivary biomarkers were identified using the area under receiving-operator curver criterion and threshold of 0.9. Xylitol and octadecanol were higher in cigarette smokers compared to controls; arabitol and maltose were higher in controls compared to cigarette smokers; octadecanol and tyramine were higher in hookah smokers compared to controls; phenylalanine was higher in controls compared to hookah smokers; and fructose, isocitric acid, glucuronic acid, tryptamine, maltose, tyramine, and 3-hydroxyisolvaleric acid were higher in hookah smokers compared to cigarettes smokers. Conclusions: The evaluation of the salivary metabolome of hookah smokers, showing separation between the groups, especially between the control versus hookah groups and cigarette versus hookah groups, and it seems to demonstrate that the use of hookah tobacco is more damaging to health.